Poster: Towards efficient spatio-temporal video grounding in pervasive mobile devices - WEERAKOON MUDIYANSELAGE, Dulanga Kaveesha (Institutional Knowledge at Singapore Management University, 2024)
As the use of pervasive devices expands into complex collaborative tasks such as cognitive assistants and interactive AR/VR companions, they are equipped with a myriad of sensors facilitating natural interactions, such as voice commands. Spatio-Temporal Video Grounding (STVG), the task of identifying the target object in the field-of-view referred to in a language instruction, is a key capability needed for such systems. However, current STVG models tend to be resource-intensive, relying on multiple cross-attentional transformers applied to each video frame. This results in runtime complexity that increases linearly with video length. Furthermore, deploying these models on mobile devices while maintaining a low-latency poses additional challenges. Hence, this paper explores the latency and energy requirements for implementing STVG models on a pervasive device.